The Own and Social Effects of an Unexpected Income Shock - Peter Kuhn; Peter Kooreman; Adriaan R. Soetevent; Arie Kapteyn (Tinbergen Institute, 2008)
Each week, the Dutch Postcode Lottery (PCL) randomly selects a postal code, and distributes cash and a new BMWto lottery participants in that code. We study the effects of these shocks on lottery winners and their neighbors.Consistent with the life-cycle hypothesis, the effects on winners' consumption are largely confined to cars and otherdurables. Consistent with the theory of in-kind transfers, the vast majority of BMW winners liquidate their BMWs.We do, however, detect substantial social effects of lottery winnings: PCL nonparticipants who live next door towinners have significantly higher levels of car consumption than other nonparticipants.
Keywords: D12; C21; 330; social interactions; natural experiments; Glücksspiel; Wertzuwachssteuer; Schock; Konsumentenverhalten; Zufriedenheit; Wohnstandort; Niederlande